Writing the feminine: women in Arab sources - Marín, Manuela; Deguilhem, Randi (The Islamic mediterranean, 2002)
Click of needles: polygamy as an issue in Arabic popular epic / Remke Kruk -- Women in medieval classical Arab poetry / Teresa Garulo -- Andalusi proverbs on women / Nadia Lachiri -- Palestinian autobiographies: a source for women's history? / Susanne Enderwitz -- Women's access to public space according to al-Muḥallā bi-l-Āthār / Camilla Adang -- Juridicial sources for the study of women: limitations of the female's capacity to act according to Mālikī law / Cristina de la Puente -- Abandoned wives and their possibilities for divorce in al-Andalus: the evidence of the Wathāʼiq works / Amalia Zomeño -- Women's history: a study of al-Tanūkhī / Nadia Mari El-Cheikh -- Women in Andalusi biographical sources / María Luisa Ávila -- A borrowed space: Andalusi and Maghribi women in chronicles / María Jesús Viguera Molíns -- Women as prophets in Islam / Maribel Fierro -- Images of Lālla ʻAwīsh: a holy woman from Marrakech / Mariëtte van Beek -- Between symbol and reality: the image of women in twentieth century Arab art / Silvia Naef
Keywords: Aufsatzsammlung; Frau; Literatur; Arabisch